Pengaruh Budaya Organisasi, Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai pada Kantor Dinas Sumber Daya Air, Cipta Karya, Tata Ruang Provinsi Sumatera Utara - Tita Arisna (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This research was conducted to examine the influence of Organizational Culture, Motivation, and Leadership Style on Employee Performance at the Spatial Planning Office of North Sumatra Province. The population in this study were 35 employees with a total sample size of 35 employees and data techniques were carried out using the Likert scale questionnaire distribution method and processed by data processor SPSS 16.0 for windows. The results showed that organizational culture, motivation on employee performance had a positive and significant partially significant effect, and leadership style had no significant effect on employee performance. Then the results showed that organizational culture, motivation and leadership simultaneously had a positive and significant effect on employee performance.